2011
DOI: 10.1007/jhep08(2011)114
|View full text |Cite
|
Sign up to set email alerts
|

General hidden conformal symmetry of 4D Kerr-Newman and 5D Kerr black holes

Abstract: There are two known CFT duals, namely the J-picture and the Q-picture, for a fourdimensional Kerr-Newman black hole, corresponding to the angular momentum J and the electric charge Q respectively. In our recent study we found a set of novel CFT duals for extremal Kerr-Newman black hole, incorporating these two pictures. The novel CFT duals are generated by the modular group SL(2, Z). In this paper we study these novel CFT duals for the generic non-extremal Kerr-Newman black hole. We investigate the hidden conf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…In fact we have found that the general picture can be set up from the hidden conformal symmetry of the generic non-extreme black holes [34].…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…In fact we have found that the general picture can be set up from the hidden conformal symmetry of the generic non-extreme black holes [34].…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…This gives two inequivalent ways of realizing the hidden conformal symmetry. In the context of Kerr/CFT this was first discussed in [30,31]; see also [32,33,34,27,35] and references therein. The central charge associated to the φ circle is…”
Section: A Myers-perry Black Holementioning
confidence: 99%
“…In order to read this picture, one just needs to turn off other charges in the thermodynamics law and find the information of dual CFT straightforwardly. Moreover, it was proposed in [25,34,35] that if there exit n charges except the mass, besides the n elementary CFT pictures there will be generic pictures generated by SL(n, Z) transformations acting on the elementary pictures. The SL(n, Z) group could be identified as a subgroup of T-duality group O(n, n, Z) [34], but it could include the electromagnetic duality, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The thermodynamics method has been checked in [23] for many well-established black hole/CFT correspondences, including three-dimensional (3D) BTZ, four-dimensional (4D) Kerr-Newman and fivedimensional (5D) Myers-Perry black holes [25,26,[32][33][34][35][36][37][38], and has also been applied to the study of holographic descriptions of black rings [23,39]. One interesting question is to understand the relation between the thermodynamics method and other conventional ways in establishing the black hole/CFT correspondence.…”
Section: Introductionmentioning
confidence: 99%